An Exploration of Quality Service in Brewing Sector. Issue 1 (2nd January 2020) - Sozen, Erol; O'Neill, Martin
ABSTRACT: Over the past three decades, there has been a spectacular change in the industrial performance and composition of the US brewing industry. Although the industry has faced conflicting reports in both the number of firms and their collective manufacturing volume, it is obvious that craft beer's production and consumption in the US are increasing. In 2017, there were more than 6, 000 craft breweries producing about 25 million barrels of beer, generating nearly $68 billion revenue and more than 456, 000 jobs. This offers a small insight into the nature and scope of the industry and its probable growth rate in the future. Of central importance to sustained growth is the consumers' perspective of both product and service quality. The popularity of the product and increasing competitiveness in this industry has yielded a heightened concern about the quality of craft-brewing services among producers and consumers. This research addresses this issue and its impact on consumers' future behavioral intentions. The study is unique in that it is the first to apply the IPA approach to the evaluation of service quality in the US craft-brewing sector. Further, it presents operators with a statistically reliable, yet user-friendly framework to address the quality phenomenon on an ongoing basis.